The Deubiquitylase USP2 Regulates the LDLR Pathway by Counteracting the E3-Ubiquitin Ligase IDOL. Issue 3 (5th February 2016) - Nelson, Jessica Kristine; Sorrentino, Vincenzo; Avagliano Trezza, Rossella; Heride, Claire; Urbe, Sylvie; Distel, Ben; Zelcer, Noam
Abstract : Rationale: : The low-density lipoprotein (LDL) receptor (LDLR) is a central determinant of circulating LDL-cholesterol and as such subject to tight regulation. Recent studies and genetic evidence implicate the inducible degrader of the LDLR (IDOL) as a regulator of LDLR abundance and of circulating levels of LDL-cholesterol in humans. Acting as an E3-ubiquitin ligase, IDOL promotes ubiquitylation and subsequent lysosomal degradation of the LDLR. Consequently, inhibition of IDOL-mediated degradation of the LDLR represents a potential strategy to increase hepatic LDL-cholesterol clearance. Objective: : To establish whether deubiquitylases counteract IDOL-mediated ubiquitylation and degradation of the LDLR. Methods and Results: : Using a genetic screening approach, we identify the ubiquitin-specific protease 2 (USP2) as a post-transcriptional regulator of IDOL-mediated LDLR degradation. We demonstrate that both USP2 isoforms, USP2-69 and USP2-45, interact with IDOL and promote its deubiquitylation. IDOL deubiquitylation requires USP2 enzymatic activity and leads to a marked stabilization of IDOL protein. Paradoxically, this also markedly attenuates IDOL-mediated degradation of the LDLR and the ability of IDOL to limit LDL uptake into cells. Conversely, loss of USP2 reduces LDLR protein in an IDOL-dependent manner and limits LDL uptake. We identify a tri-partite complex encompassing IDOL, USP2, and LDLR and demonstrate that in this context USP2 promotes deubiquitylation of the LDLR and prevents its degradation. Conclusions: : Our findings identify USP2 as a novel regulator of lipoprotein clearance owing to its ability to control ubiquitylation-dependent degradation of the LDLR by IDOL. Abstract : Supplemental Digital Content is available in the text.